Tahapan Evaluasi Program Bimbingan dan Konseling di Masyarakat dan Pengembangan Menjadi Program Bimbingan dan Konseling Yang Islami, Efektif Dan Efisien - Dipa, Laudza Zulfa Nur (Institut Agama Islam Negeri Padangsidimpuan, 2024)
The essence of implementing a guidance and counseling program evaluation can help improve and develop guidance and counseling programs in knowing the development of counselors' attitudes, behavior and potential development in a better direction. So the implementation of guidance and counseling program evaluation must be systematic and gradual, so that implementation can be directed and measurable from the results of the program evaluation. However, the reality today is that there are still guidance and counseling practices that do not carry out evaluations of guidance and counseling programs, especially among the community. So as a result of not carrying out an evaluation of the guidance and counseling program, individuals will not know the extent of the potential or development that exists in a counselor and the surrounding environment. Especially among the community who are minimal in carrying out program evaluations, there is a great need for development and improvement in programs in the environment. Therefore, it is highly recommended that the evaluation stage of the guidance and counseling program be carried out in the community. The context of evaluating the guidance and counseling program will not only focus on general discussions, but will discuss the stages of evaluating an effective and efficient Islamic perspective which was always carried out by the Prophet Muhammad through evidence from the Qur'an and As-Sunnah. So this article aims to describe the stages of evaluating guidance and counseling programs in the community and developing them into Islamic, effective and efficient guidance and counseling programs.